Climate Change and the Economic Balance of Public Health in Indonesia - Ulhaq, Muhammad Zia; Al Fajar, Muhammad Rasyad; Ibrahim, Ibrahim; Nursyafika, Nursyafika; Afriani, Jaitun; Al-Ifansyah, M.; Dianti, Nurul Jumar (Indonesian Journal Publisher, 2025)
Developing countries like Indonesia have been facing huge challenges with climate change, especially in terms of maintaining a balance between economic growth and public health. Increasing infectious diseases, respiratory disorders, and economic losses are caused by climate change impacts such as rising temperatures, extreme rainfall, and natural disasters. The purpose of this research is to see how climate change affects public health and how it impacts the economic stability of the health sector in Indonesia. This research utilizes a qualitative-descriptive approach that uses secondary data from various sources. The research shows that economic losses due to climate change in the health sector reach trillions of rupiah every year, and the poor are the most affected. To maintain the balance between economic development and public health in the future, adaptation and mitigation strategies are essential.